2017
DOI: 10.1007/s10753-017-0540-6
|View full text |Cite
|
Sign up to set email alerts
|

2,3-Diarylxanthones as Potential Inhibitors of Arachidonic Acid Metabolic Pathways

Abstract: Abstract-In response to an inflammatory stimulus, arachidonic acid (AA), the main polyunsaturated fatty acid present in the phospholipid layer of cell membranes, is released and metabolized to a series of eicosanoids. These bioactive lipid mediators of inflammation arise physiologically through the action of the enzymes 5-lipoxygenase (5-LOX) and cyclooxygenases (constitutive COX-1 and inducible COX-2). It is believed that dual inhibition of 5-LOX and COXs may have a higher beneficial impact in the treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…A more exciting result was that licofelone inhibited IL-18-induced mesangial cell proliferation, and the results indicated that licofelone might be effective for the treatment of glomerulonephritis in children [201]. 2,3-diarylxanthones, dual inhibitors of COX and 5-LOX, are capable of preventing the production of LTB 4 in human neutrophils as well as decreasing PGE 2 production in human whole blood in a concentration-dependent manner [235]. According to the current results, the effect of lox-related drugs in regulating inflammation is still in the experimental study stage.…”
Section: Treatmentsmentioning
confidence: 99%
“…A more exciting result was that licofelone inhibited IL-18-induced mesangial cell proliferation, and the results indicated that licofelone might be effective for the treatment of glomerulonephritis in children [201]. 2,3-diarylxanthones, dual inhibitors of COX and 5-LOX, are capable of preventing the production of LTB 4 in human neutrophils as well as decreasing PGE 2 production in human whole blood in a concentration-dependent manner [235]. According to the current results, the effect of lox-related drugs in regulating inflammation is still in the experimental study stage.…”
Section: Treatmentsmentioning
confidence: 99%
“…This indicates that the mechanistic action of JSALF could be connected to the prevention of leukotriene and prostaglandins production through lipoxygenase and cyclooxygenase pathways since the sensitivity of arachidonic acid to LOX are more than that of COX enzyme [45,46]. Two-fold inhibitors of both LOX and COX enzymes such as diclofenac and 2,3-diarylxanthones can prevent the production of leukotriene B 4 (LTB 4 ) as well as Prostaglandin E 2 (PGE 2 ) [49,50]. LTB 4 mediates leukocytes activation in inflammation whereas PGE 2 produces the five manifestations of inflammation which include fever, swelling, redness, immobility, and pain.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that numerous external and internal factor have the tenacity to activate the phospholipase A 2 (PLA 2 ). This activation cleaves the membrane bound AA from the phospholipids and makes it available for three major inflammatory pathways including cytochrome P-450 monooxygenase (Capdevila et al, 2000 ; De Montellano, 2005 ), lipoxygenase (Piomelli et al, 1987 ), and cyclooxygenase pathway (Kuehl and Egan, 1980 ; Santos et al, 2017 ).…”
Section: Cyclooxygenase Pathwaymentioning
confidence: 99%